Determination of optimum glycetol equilibration time of bull semen - ΚΟΥΤΣΟΥΡΗΣ, XP. Δ.; ΝΙΚΟΛΑΪΔΟΥ-ΒΑΡΕΛΛΑ, ΑΔ. (Journal of the Hellenic Veterinary Medical Society, 2019)
A total of 320 semen samples from 64 sires of the Br. Swiss, Holstein, Charolals and Simmental breed, aged 2 - 1 0 years, were examined for the purpose of determining the optimum glycerol equilibration time. The semen to the above bulls was frozen And the percentage of spermatozoa revival was estimated, after an equilibration time of 0, 1, 3, 5, *7, 9, 11, 13, and 24 hours. The results obtained can be summarized as follows: 1. There was a significant difference (P<0.05) in the percentage of revival, after equilibration at various time intervals. 2. The optimum glycerol equilibration time fluctuated and varied between 7 - 1 3 hours (8.7+2,58). 3. The fluctuation of the optimum glycerol equilibration time, both among breeds and among bulls of different age, was not significant Determination of optimum glycerol equilibration time of the semen of the bulls of the station may serve as a criterion for their classification in groups, which will ultimately result in obtaining batches of frozen semen of better quality and higher conception rate.